Automated photovoltaic irrigation system for crops in the Colombian Caribbean Region (2024)
The project presents a proposal for the design and implementation of an automated photovoltaic irrigation system for crops in the Caribbean region of Colombia. The main motivation is to address the challenges related to water use in agriculture and the lack of access to electricity in some rural areas. This system uses the principles of precision agriculture by collecting and processing real-time data on weather and soil conditions using a network of sensor nodes distributed throughout the crop area. As a solution, a solar-powered automated irrigation system based on a wireless sensor network (WSN) was designed to remotely monitor soil moisture and temperature. In the proposed system, relevant weather and soil parameters are collected by a wireless sensor network and transmitted to a base station. The base station processes the collected data and executes irrigation control algorithms to improve water use. The system is powered by solar energy, making it viable in areas without access to the electrical grid. The implementation of this automated and sustainable irrigation system not only contributes to improved agricultural productivity and water conservation, but also lays the groundwork for the adoption of precision agriculture practices in the Colombian Caribbean region. By combining innovative technologies such as sensor networks, IoT and renewable energy, this project represents a significant step towards more efficient, productive and environmentally friendly agriculture.